Adsorption of Carbon Dioxide in Several Aged Hydrotalcites and Calcined Hydrotalcites: Influence of Microwave Irradiation during the Ageing Step on Their Basic Properties - Olga Bergadà; Pilar Salagre; Yolanda Cesteros; Francisco Medina; Jesús E. Sueiras (Adsorption Science & Technology)
Several Ni/Mg/Al hydrotalcites were aged by autoclaving under microwave irradiation, refluxing under microwave irradiation and by traditional refluxing methods. The hydrotalcite aged by autoclaving under microwave irradiation at a higher temperature (453 K) and for a longer time (120 min) exhibited a higher surface area and a higher basicity than the hydrotalcites aged by refluxing under microwave irradiation or by traditional refluxing. This can be explained by the generation of surface-defective sites accompanied by a loss of aluminium due to the effect of microwave irradiation. However, after calcination, high-area mixed oxides obtained from hydrotalcites aged by refluxing under microwave irradiation exhibited a higher basicity per square metre than those obtained from hydrotalcites aged under more drastic conditions. For the hydrotalcites aged under microwave irradiation, this may be related to the surface characteristics of the amorphous alumina generated during calcination. The sample with the lowest amount of alumina was that obtained from the hydrotalcite which had been aged at a higher temperature and for a longer time.